A revision of Chinese pear psyllids (Hemiptera: Psylloidea) associated with Pyrus ussuriensis - Luo, Xinyu; Li, Fasheng; Ma, Yanfang; Cai, Wanzhi (Zootaxa, 2012)
The Chinese pear psyllids, Cacopsylla spp., associated with Pyrus ussuriensis are reviewed. Three new species, C. accincta sp. n., C. burckhardti sp. n., and C. cinereosignata sp. n., are described. Cacopsylla liaoli (Yang & Li), C. qiuzili Li, C. maculatili Li and C. chinensis (Yang & Li) are redescribed. A key to the adults of the seven species and a key to nymphs of three species are given.